Future CO2 emissions and electricity generation from proposed coal‐fired power plants in India. Issue 4 (25th April 2017) - Shearer, Christine; Fofrich, Robert; Davis, Steven J.
Abstract: With its growing population, industrializing economy, and large coal reserves, India represents a critical unknown in global projections of future CO2 emissions. Here, we assess proposed construction of coal‐fired power plants in India and evaluate their implications for future emissions and energy production in the country. As of mid‐2016, 243 gigawatts (GW) of coal‐fired generating capacity are under development in India, including 65 GW under construction and an additional 178 GW proposed. These under‐development plants would increase the coal capacity of India's power sector by 123% and, when combined with the country's goal to produce at least 40% of its power from non‐fossil sources by 2030, exceed the country's projected future electricity demand. The current proposals for new coal‐fired plants could therefore either "strand" fossil energy assets (i.e., force them to retire early or else operate at very low capacity factors) and/or ensure that the goal is not met by "locking‐out" new, low‐carbon energy infrastructure. Similarly, future emissions from the proposed coal plants would also exceed the country's climate commitment to reduce its 2005 emissions intensity 33% to 35% by 2030, which—when combined with the commitments of all other countries—is itself not yet ambitious enough to meet the international goal of holding warming well below 2°C relative to the pre‐industrial era. Key Points: India's currently proposed coal plants exceed its future projected energy demand India will have a hard time meeting its climate goals given its current coal plant proposals India's current coal proposals risk either locking out lower‐carbon energy and/or being stranded assets